Academic and educational development : research, evaluation and changing practice in higher education - Macdonald, Ranald, 1952-; Wisdom, James (Staff and educational development series., 2002)
Part of the well-known Staff and Educational Development Series, this practice oriented book brings together leading research and evaluation approaches and supporting case studies from leading educational researchers and innovative teachers.